Tax Farming As Panacea for Increased Revenue Generation in Nigeria - Ikechi, Joseph, Fineboy; Chinyere, Akujor, Jane; Odii, Nwankwo, Kelechi (International Journal Of Management And Economics Invention, 2022)
This study examines tax farming as panacea for increased revenue generation in Nigeria. Ineffective tax administration appears to be an unending setback in Nigeria as a result of myriad of challenges resulting in poor tax revenue generation. The study reviewed many previous studies on tax farming. The reviews revealed that tax farming leads to excessive exploitation of taxpayers in their bid to overzealously recover the advance payment to the government and running expense and then make profit. It was uncovered that the unpredictability and volatility of tenure of tax farmers results in lack of investment in the system because tax-farmers investments were not secured as their contract could be terminated by the state at any time thereby discouraging investment in the long-run. However, the advantages far outweigh the demerits. The study revealed that tax farming is in line with privatization, the current economic drive where the management of hitherto public enterprises has been transferred to competent private individuals to ensure efficiency and effectiveness of such organizations. Again, it ensured a highly coherent and efficient system of resource allocation. The system similarly provided guidance for resource allocation not only to the tax-farmers but also to the state. The tax-farming system was a very efficient revenue collection tactic for the state. It played a substantial role behind the decision of the state to invest directly in the various industries where it generated enormous tax revenue. The tax-farming system contributed significantly to the increase in capital in the private sector both by the massive profits it helped create and by compelling the entrepreneurs to form partnerships. Based on the findings via review of relevant literatures, the study recommends that tax farming should be introduced by the government and given legal backing in Nigeria as a veritable strategy for taxes and levies collection. Government should concentrate on tax administration which involves interpretation of the law and issuing guidelines, assessment, and auditing to ensure fairness and the rule of law which will entrench significant degree of monitoring of the government’s agents while tax collection should be contracted out to tax farmers in the collection of determined tax arrears in order to stop over-collection. They should be engaged verification of value of goods declared by importers at customs to ensure that it corresponds to international price data. This would guarantee efficient revenue collection and accountability since the amount to be collected is already determined. The bidding and auctioning off process of tax farming to determine the right of private sector collectors to collect certain taxes and levies should be competitive and transparent to ensure that maximum revenue is derived from the system and to avoid corrupt leaders ceding the right to collect taxes and levies to their cronies, a practice which negates the primary objectives of tax farming. The bidding process should be done at arm’s length.